Gross morphology and osteometry of the ribs of Etawah crossbred goats - SUHARSONO SUHARSONO; YENI DHAMAYANTI; HANA ELIYANI; SARMANU SARMANU; LINTANG WINANTYA FIRDAUSY; SALIPUDIN TASIL MASLAMAMA; MUHAMMAD THOHAWI ELZIYAD PURNAMA (Society for Indonesian Biodiversity, 2025)
Abstract. Suharsono, Dhamayanti Y, Eliyani H, Sarmanu, Firdausy LW, Maslamama ST, Purnama MTE. 2025. Gross morphology and osteometry of the ribs of Etawah crossbred goats. Biodiversitas 26: 1691-1697. The ribs have several vital purposes, including protecting the contents of the mediastinum and thoracic cavity, moving superiorly, inferiorly, anteriorly, and posteriorly to aid in breathing, serving as a site for the origin or attachment of certain muscles, and aiding in erythropoiesis during development. However, ribs comprise the first to thirteenth bones with different areas. This study aimed to evaluate the gross anatomy and morphometry of the ribs of Etawah crossbred goats (Capra aegagrus hircus) using Multivariate Adaptive Regression Splines (MARS) modeling. A total of 299 ribs from 23 adult male Etawah crossbred cadavers were investigated in this study. Each rib was identified in order from the first to the thirteenth ribs. Rib evaluation was performed on the following i.e., Width of the Tubercle Costochondral (WTC), Width of the Junction Costochondral (WJC), and Length of the Costochondral (LC). Data were calculated using Multivariate Adaptive Regression Splines (MARS) modeling. As a result, gross anatomically, all Etawah crossbred ribs were composed of the costal cartilage at the distal end and the head, neck, and tubercle at the proximal end, shaft, or body. The WTC and WJC sizes revealed an evident decrease from the first to the second rib and then a gradual decrease on the thirteenth rib. Meanwhile, the LC's size revealed a gradual increase from the first to the eighth rib and gradually decreased on the thirteenth rib. In conclusion, using the LC variable, the eighth rib was determined to be a transition location. The eighth rib may be used as a biometric orientation point in the thoracic region since it is identified as the widest bone, particularly for estimating body weight and body condition scores.